2013
DOI: 10.1186/1757-2215-6-12
|View full text |Cite
|
Sign up to set email alerts
|

Insulin and insulin-like growth factor signaling increases proliferation and hyperplasia of the ovarian surface epithelium and decreases follicular integrity through upregulation of the PI3-kinase pathway

Abstract: BackgroundThe ovarian surface epithelium responds to cytokines and hormonal cues to initiate proliferation and migration following ovulation. Although insulin and IGF are potent proliferative factors for the ovarian surface epithelium and IGF is required for follicle development, increased insulin and IGF activity are correlated with at least two gynecologic conditions: polycystic ovary syndrome and epithelial ovarian cancer. Although insulin and IGF are often components of in vitro culture media, little is kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 47 publications
3
14
0
Order By: Relevance
“…To investigate the potential target gene which miR-217 could regulate in ovarian cancer cells, we used two publicly available algorithms (Targetscan6.2 and miRanda) to predict miR-217 targets in EOC. Among the candidate target genes, IGF1R attracted our attention since it functions as an oncogene in various cancers, including ovarian cancer (15). As shown in Fig.…”
Section: Igf1r Is a Direct Target Of Mir-217mentioning
confidence: 99%
“…To investigate the potential target gene which miR-217 could regulate in ovarian cancer cells, we used two publicly available algorithms (Targetscan6.2 and miRanda) to predict miR-217 targets in EOC. Among the candidate target genes, IGF1R attracted our attention since it functions as an oncogene in various cancers, including ovarian cancer (15). As shown in Fig.…”
Section: Igf1r Is a Direct Target Of Mir-217mentioning
confidence: 99%
“…Histological analyses were performed according to a previously published study [31]. Primary antibodies utilized in this study included Ki67 (Abcam, Cambridge, MA), PR, ERα and Hand2 (Santa Cruz Biotechnology, Santa Cruz, CA) [32].…”
Section: Methodsmentioning
confidence: 99%
“…Ozden-Akkaya and et al, (2017) injected methoxychlor to fetal and neonatal rats and they found that IGF-I expression increased in granulosa cells. On the other hand, the increase in IGF-I expression in interstitial cells was directly related to the polycystic ovary syndrome (Schildkraut et al, 1996;King et al, 2013). To our knowledge, the studies have been conducted on the expression of IGF-I and IGF-IR after CAP treatment on ovarian granulosa cells have not been reported.…”
Section: Discussionmentioning
confidence: 93%